The Antifungal Potential of Stevia rebaudiana Bertoni Leaf Extract Against Candida albicans - Herawati, Margaretha; Deviyanti, Sinta; Ferhad, Adibah (Journal of Indonesian Dental Association, 2021)
Candida sp. are eukaryotic opportunistic pathogens that reside on the mucosa oral cavity, gastrointestinal tract, vagina and sometimes skin. An infection caused by Candida is termed candidiasis or candidosis. Oral candidiasis is a common opportunistic infection of the oral cavity caused by overgrowth of Candida species, the most common being Candida albicans. Risk factor for oral candidiasis are local factors, systemic factors and the physiological states. The most commonly used classes of antifungal drug treatment to Candida infections are the azole, polyenes and echinocandins. However, the management of Candida infections faces many problems, such as toxicity, resistance of Candida to antifungal drugs, relapse to Candida infection and the high cost of antifungal drugs. Many investigators are exploiting alternative therapeutic strategies to overcome problems treating candidiasis. Stevia leaves extracts has been known to have antifungal activity to treat candidiasis. The aim of this review article is to explain antifungal potency of Stevia rebaudiana Bertoni leaves extracts toward Candida albicans. Stevia rebaudiana Bertoni leaves extracts can use as cheap, natural and alternative agent to control candidiasis.